2016
DOI: 10.1021/jacs.6b07932
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Ce(IV) Oxo Complex via Inner Sphere Nitrate Reduction

Abstract: (3), confirming the nucleophilic character of its oxo ligand. Natural bond orbital and quantum theory of atoms-in-molecules data reveal the Ce-O interaction in 1 to be significantly covalent, and strikingly similar to analogous U-O bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 47 publications
5
42
2
Order By: Relevance
“…More recently, Damon et al have reported a Ce(IV) oxo complex with pronounced covalent bond character. 73 Based on analysis of the PBE-derived density, a r BCP value of 0.196 a.u. was found for the Ce-O bond.…”
Section: U-like Covalency In Ce Compoundsmentioning
confidence: 99%
“…More recently, Damon et al have reported a Ce(IV) oxo complex with pronounced covalent bond character. 73 Based on analysis of the PBE-derived density, a r BCP value of 0.196 a.u. was found for the Ce-O bond.…”
Section: U-like Covalency In Ce Compoundsmentioning
confidence: 99%
“…Many aspects of these studies challenge the traditional viewpoints that the 4f electrons are entirely localized on the lanthanide and that bonding with the oxide ligands is best described using electrostatic models. Qualitatively, invoking a degree of covalent Ln-O bonding in LnO 2 could be justified given the growing number of synthetic, [38][39][40][41][42][43][44][45][46] magnetic, [47][48][49][50][51][52][53] spectroscopic, [54][55][56][57][58][59][60] and theoretical 30,[61][62][63][64][65][66][67] studies indicating that strictly ionic models of lanthanide bonding are inadequate. For example, a new class of compounds has emerged containing lanthanide and other rare earth metals bound to oxo, 38,[68][69] imido, [70][71][72][73] and carbene ligands, [74][75][76][77] among others.…”
Section: Introductionmentioning
confidence: 99%
“…3 Additionally, our group reported the synthesis of the cerium( iv ) oxo complex, [Li(12-crown-4)][(NNâ€Č 3 )Ce(O)] ( II , NNâ€Č 3 = N(CH 2 CH 2 NR) 3 , R = Si t BuMe 2 ), which was synthesized by thermal decomposition of a Ce( iii ) nitrate precursor [Li(12-crown-4)][(NNâ€Č 3 )Ce( Îș 2 -O 2 NO)]. 8 More recently, Schelter and co-workers reported the synthesis of a Ce( iv ) oxo supported by the tripodal TriNOx ligand, [(TriNOx){Ce(O)}Rb] 4 ( III ). 5 Also of note is [M] 2 [Ce(ÎŒ-O)(NR 2 ) 3 ] 2 ( IV , M = Na, K; R = SiMe 3 ), reported by Lappert and co-workers in 2010.…”
Section: Introductionmentioning
confidence: 99%
“…3 Similarly, the oxo ligands in II and III are stabilized by their interactions with a capping alkali metal counterion. 5 , 8 The prevalence of these non-covalent interactions can be rationalized by the poor overlap of the metal f and d orbitals with oxygen 2p orbitals, which results in weak π bonds within the Ce O fragment, concomitant with considerable oxo nucleophilicity. 4 , 9 – 11 Indeed, controlling this nucleophilic character has been one of the key challenges to synthesizing a terminal lanthanide oxo complex.…”
Section: Introductionmentioning
confidence: 99%